Joint 2D-DOA and Frequency Estimation for L-Shaped Array Using Iterative Least Squares Method - Ling-yun Xu; Xiao-fei Zhang; Zong-ze Xu; Miao Yu (International Journal of Antennas and Propagation)
We introduce an iterative least squares method (ILS) for estimating the 2D-DOA and frequency based on L-shaped array. The ILS iteratively finds direction matrix and delay matrix, then 2D-DOA and frequency can be obtained by the least squares method. Without spectral peak searching and pairing, this algorithm works well and pairs the parameters automatically. Moreover, our algorithm has better performance than conventional ESPRIT algorithm and propagator method. The useful behavior of the proposed algorithm is verified by simulations.